Suicidal ideation in emerging and young adults: latent profile analysis of risk and protective factors in a nationally representative sample - Love, Heather Autumn (Kansas State University, 2019)
Each year in the United States, 40,000 individuals die by suicide, 7,000 of whom are young adults between the ages of 25-34. For every death, it is estimated that another 25 suicide attempts are made and that over 8% of young adults experience thoughts of suicide each year. Suicide rates are climbing, but identification of protective factors to reduce suicide risk remains elusive. Using a sample of 4,208 young adults from the National Longitudinal Study of Adolescent to Adult Health, a latent profile analysis was used to test the number of profiles that best fit the data based on indicators that were hypothesized to be risk or protective features, and those profiles were analyzed using logistic regression to assess suicide risk. Hypothesized protective indicators included parent and romantic relationship quality, parental satisfaction, job satisfaction, and religiosity. Hypothesized risk indicators included parental demands, depressive symptoms, job demands, isolation, alcohol use, and adverse childhood experiences. A four-profile solution was optimal for this data and yielded four distinct profiles named: Satisfied with Life (n = 2,442), Relationship Stress (n = 669), Demanding Jobs (n = 658), and Challenging Childhood (n = 427). Individuals in the Satisfied with Life profile reported positive relationship quality with parents, partners, and children, and low depressive symptoms, isolation, and adverse childhood experiences. This profile was associated with a 60% decrease in risk for suicidal ideation. Participants in the Relationship Stress profile reported low relationship satisfaction, lack of confidence that their romantic relationship was going to be permanent, and high alcohol consumption. Individuals in this profile were 104% more likely to experience suicidal ideation compared to those not in this profile. The Demanding Jobs profile included individuals who felt their work interfered with their family time, and vice versa, but still had moderately high satisfaction in each area. This profile was not significantly associated with suicidal ideation. The final profile, Challenging Childhood, included individuals who reported low quality of relationships with their parents, high levels of isolation and depressive symptoms, and significantly higher adverse childhood experiences than other individuals in this sample. Individuals in this profile were associated with 192% increase in risk for suicidal ideation than those not in this profile. The results of this study underscore the importance of positive relationships as a protective factor against suicide, and provide new information about how job satisfaction and demands can also serve as protective features. Therapeutic interventions that address improving social support, coping with traumatic events, and decreasing alcohol consumption are recommended to decrease suicidal thoughts.
Keywords: Suicidal ideation; Mental health; Young adult; Interpersonal relationships